Fotoperíodo crítico e filocrono para produção de diferentes cultivares de crisântemo de corte - Zago, Andressa Pozzatti (2017)
Cutting chrysanthemum (Dendranthema grandiflora Tzvelev) is a photoperiod sensitive crop that requires artificial lighting during winter cultivation, around four weeks, leaving the plants in a long day condition to carry out inhibition to flowering, Vegetative growth. Due to this it is necessary a great consumption of electrical energy, frequent replacements of lamps due to their short useful life, which raises the production costs for the producer and damages the environment. In order to minimize these excesses, the objective of this work was to estimate the critical and phyllochron photoperiod for Furore Golden, Snowdon and Yellow Tsuky chrysanthemum cultivars and to perform the phyllochron growth and estimation analysis for the Jô Spitoven cultivar. Two experiments were carried out in a protected environment in the UFSM Floriculture Sector. The first in the period from July to October 2015, in a completely randomized design, with four replications and the treatments were the cultivation of chrysanthemum cv. Jô Spitoven using the photoperiods of 14h, 14h and 30min, 15h and 15h and 30min of light under continuous and intermittent artificial lighting. The second experiment was conducted in the period from July to October 2016, in a completely randomized design, with five replications and cvs. Furore Golden, Snowdon and Yellow Tsuky, cultivated with photoperiods of 12h and 30min, 13 h, 14 h and 16 h. Plant height, number of leaves, leaf area, stem and inflorescence diameter and fresh and dry phytomass of the inflorescence and total plant height were evaluated. The photoperiod of 12 h and 30 min was estimated as the critical photoperiod of the cultivars Furore Golden, Snowdon and Yellow Tsuky, phyllochron values estimated in cv. Furore Golden varied according to the different photoperiods, the same did not occur in the others. The growth analysis of cv. Jô Spitoven, showed better results in handling with intermittent lighting, especially the photoperiod of 14h and 30min, which also presented phyllochron less than the others.